Students’ Perspective on the Use of Google Sites in General English Class at Higher Education - Atik Ulinuha; Tantry Ajeng Parnawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Technology plays a significant role in English Language Teaching during the pandemic. There are several platforms that both teachers and students need to adapt to. Google seems to have a major role in developing platforms for both teachers and students. However, among those platforms, this study focuses on the use of E-Module arranged using the Google Sites platform as supplementary material in General English classes. Google Sites was chosen as it is a web-based module that teachers can personalize to fulfill students’ needs. Since this study aims to evaluate the use of E-Module arranged using the Google Sites platform as supplementary material in General English classes at Tribhuwana Tunggadewi University, this study employed descriptive quantitative method using survey to gather the data. The population of the study was all students who enroll in General English during the academic year 2021/2022. From the population, 328 students participated in the survey. The survey questions covered learning efficiency, experience, and motivation from students’ points of view. The study findings indicated that more than half of respondents agreed that the module was very good to use without revision, which means the module was efficient, fun, and motivating. Yet, the average of 25% of each question demands minor improvement for the module as well as providing the printed version. Therefore, teachers and lecturers may use Google Sites as supplementary material. For further study, as the pandemic becomes endemic, researchers might conduct an evaluation of e-module both in online and offline classes.Keywords: E-nglish Module, Google Sites, Students’ Perspective